21 C1–C2 Joint Osteotomy and Reduction of Craniovertebral Junction Deformity (Cervical Spine Deformity Surgery, 2019)
Craniovertebral junction (CVJ) deformity is a rare and challenging pathology that can result in progressive deformity, myelopathy, severe neck pain, and functional disability, such as difficulty swallowing. The most common causes of CVJ deformity include rheumatoid arthritis, trauma, neoplasm, infection, and congenital bony malformation. This deformity may alter the quality of life because of the neck pain, disabling headache, dysphagia, and myelopathy. Surgical management of CVJ deformity is complex for anatomical reasons; given the sensitive relationships involved in the surrounding neurovascular structures and intricate biomechanical issues, access to this region is relatively difficult. Evaluation of the reducibility of the upper cervical spine, CVJ alignment, and direction of the mechanical compression may determine surgical strategy. If CVJ deformity is reducible, posterior in situ fixation may be a viable solution. If the deformity is rigid and C1–C2 facet is fixed, osteotomy may be necessary to make the C1–C2 facet joint reducible. C1–C2 facet release with vertical reduction technique could be useful especially when the C1–C2 facet joint is the main pathology of CVJ kyphotic deformity or basilar invagination (BI). The indications for transoral surgery as a treatment for CVJ deformity are decreasing. However, transoral decompression and subsequent posterior fixation are still available surgical options when CVJ deformity is irreducible and ventral bony compression is prominent. In this chapter, we review several cases of CVJ deformity, including BI, fixed atlantoaxial dislocation, and fixed CVJ kyphosis. Moreover, we also present a discussion of CVJ alignment and various strategies for the management of this complex disease entity, as well as possible ways to prevent complications and improve surgical outcomes.
Keywords: craniovertebral junction; cervicomedullary junction; alignment; basilar invagination; fixed deformity; atlantoaxial dislocation; osteotomy; joint distraction; vertical reduction